The impact of implementation of supply chain management policy in the Department of Local Government and Housing in Limpopo Province - Marokana, Matsobane David (University of Limpopo (Turfloop Campus), 2012)
This study focused on the impact of implementation of Supply Chain Management Policy (SCM) in Limpopo Department of Local Government and Housing (The Department of Local Government and Housing is officially known as the Department of Co-operative Governance, Human Settlements and Traditional affairs as from the 16 August 2011).The study analyzed the impact of implementation of SCM policy including the implications of non-compliance with this policy. The study also provides an analysis of the perceptions of officials of the Department of Local Government and Housing with regard to the impact of implementation of Supply Chain Management policy. The study also looked at Supply Chain Management in a public sector context including mechanisms that can be employed in order to improve implementation of Supply Chain Management policy. Qualitative research methods were used in this study. This means that primary data was collected using interviews and questionnaires. The findings from the study indicated that the Department experienced challenges in implementing the SCM policy and that there was a significant change in the behavioural patterns of the certain employees after the SCM policy was implemented. The study also revealed that the implementation of SCM policy had both positive and negative effects on the employees of the Department, service providers as well as the public. Furthermore, the research revealed that violation of SCM policy has a negative impact on service delivery. The study has provided answers to both the main research question and sub-questions. From the findings made, the study concluded that the implementation of Supply Chain Management policy has both the negative and positive impact on the Department.
Thesis (MPA.) --University of Limpopo (Turfloop Campus), 2012
Keywords: Supply chain management; Procurement; Government purchasing -- South Africa -- Limpopo; Industrial procurement -- South Africa -- Limpopo; Business logistics; Purchasing departments